ACTIVATED NATURAL ZEOLITES FOR PETROLEUM HYDROCARBONS ADSORPTION - HOAGHIA, Maria-Alexandra; ASCHILEAN, Ioan; BĂBĂLĂU-FUSS, Vanda; BECZE, Anca; CADAR, Oana; ROMAN, Cecilia; ROMAN, Marius; SENILA, Marin; KOVACS, Eniko (Studia Universitatis Babeș-Bolyai Chemia, 2021)
This study was carried out with the aim of increasing and determining the activated zeolites’ adsorption capacity by testing their efficiency on petroleum hydrocarbons. Natural zeolite samples were sequentially studied after thermal and chemical activations. The results indicated that after the activations, the zeolite samples gained an increasing adsorption capacity of petroleum hydrocarbons. Furthermore, the zeolites with small particulate sizes (<10 µm) have a higher adsorption capacity than the zeolites with a granulometry of 1-3 mm. The metal content ranged between 4200-7400 mg/kg Na, 15090-22990 mg/kg Ca, 2670-3950 mg/kg Mg, 19470-19670 mg/kg K, 6140-7210 mg/kg Fe and 149-178 mg/kg Mn. Mineralogical analyzes (X-ray diffraction - XRD and scanning electron microscopy - SEM) were applied for the characterization of the zeolites. According to the XRD results, the zeolites are characterized by a 64 % crystallization level. The main mineral which was determined was Clinoptilolite-Ca. The SEM micrographs indicate the morphology of zeolite surfaces.